Design and experimentation of a solar-powered robot for cleaning the greenhouse roofs - Amin, Ahmed; Wang, Xiaochan; Guoxiang, Sun; Shi, Yinyan; Ndumiaassan, Joseph Ndiithi; Okasha, Mahmoud (Results in engineering, 2024)
Greenhouse technology is crucial for combating climate change and enhancing off-season produce and crop yield. Dust build-up on greenhouse roofs remains a significant problem, significantly reducing light transmission and affecting plant growth. Therefore, this study aims to classify dust build-up on greenhouse roofs and to address it by designing, manufacturing, operating, and evaluating a solar-powered cleaning robot system. Water and cement removal agent (CRA) with different mixing ratios were selected to clean the greenhouse roof. The initial findings demonstrate the greenhouse cover's ability to allow light to pass through can differentiate between different levels of dust accumulation. This study reveals that 88 %–93 % of transmittance levels indicate a clean roof, 82 %–87 % reveal minor dust accumulation, 81 %–75 % denote moderate dust accumulation, and below 75 % signify major dust accumulation. This increased the efficiency of the light intensity for minor dust roofs from 39,285 to 41,731 lux ((CRA) 1:3 water), moderate dust roofs from 36,777 to 39,383 lux ((CRA) 1:1 water), and major dust roofs from 30,585 to 35,525 lux (CRA). The results show a substantial improvement in light transmittance from 88 % to 93 % for clean roofs, compared to much lower levels for dust-accumulated roofs. [Display omitted] •Innovative solar-powered robot design for automated greenhouse roof cleaning.•Enhanced cleaning raises light transmittance from 88 to 93 %, improving plant growth.•The robot delivers effective cleaning for multi-span greenhouse types.